Public-sector efficiency and interjurisdictional competition: An empirical investigation - Daniel Thomas Becker (Universität Rostock, Institut für Volkswirtschaftslehre, 2008)
This paper investigates the performance and efficiency of the public sector in 74 countries worldwide for the years 1985, 1990, 1995 and 2000. Similar to what is done in Afonso / Schuhknecht / Tanzi (2005, Public Choice), I calculate performance measures for various fields of government policy, including education, health, security or macroeconomic stability. These performance measures are then used as output variables in a non-parametric FDH (free disposable hull) and DEA (data envelopment analysis) approach for the calculation of efficiency scores. Government expenditure is used as input for the evaluation of efficiency. In the last step the efficiency scores are regressed upon variables that describe the environment of government policy. I find that smaller public sectors tend to be more efficient, but the effect is not very sizeable. The same is true for countries that are more globalised. The pattern of (in-)efficiency can be large explained by continent-dummies.
Keywords: C14; H50; 330; Public-Sector Efficiency; Free Disposable Hull; Data Envelopment Analysis; Öffentlicher Sektor; Öffentliche Ausgaben; Technische Effizienz; Data-Envelopment-Analyse; Vergleich; In